Extracellular AMP Suppresses Endotoxemia-Induced Inflammation by Alleviating Neutrophil Activation - Hua, Ye; Liu, Dadong; Zhang, Danyi; Wang, Xu; Wei, Qing; Qin, Weiting (Frontiers in Immunology, 2020)
Intracellular adenosine monophosphate (AMP) is indispensable for cellular metabolic processes, and it is interconverted to ADP and/or ATP or activates AMP-activated protein kinase (AMPK). However, the specific biological function of extracellular AMP has not been identified. We evaluated the effect of extracellular AMP using in vivo and in vitro models of endotoxemia. We found that AMP inhibited inflammation and neutrophil activation in lipopolysaccharide (LPS)-induced endotoxemic mice. The effects of extracellular AMP were abolished by an adenosine 1 receptor (A1R) antagonist but were not influenced by inhibiting the conversion of AMP to adenosine (ADO), indicating that AMP inhibited inflammation by directly activating A1R. In addition, in vitro experiments using LPS-stimulated mouse neutrophils showed that AMP inhibited LPS-induced reactive oxygen species (ROS) production, degranulation and cytokine production, while the effects were reversed by an A1R antagonist. Further research showed that AMP regulated LPS-stimulated neutrophil functions by inhibiting the p38 MAPK pathway. These findings were also confirmed in primary neutrophils derived from healthy human blood. Moreover, we collected serum samples from septic patients. We found that AMP levels were increased compared with those of healthy volunteers and that AMP levels were negatively correlated with disease severity. Together, these data provide evidence that extracellular AMP acts on A1R to suppress endotoxemia-induced inflammation by inhibiting neutrophil overactivation and that the p38 MAPK signaling pathway is involved.